2019
DOI: 10.1186/s12889-019-7469-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing awareness of food-choking and nutrition in children through education of caregivers: the CHOP community intervention trial study protocol

Abstract: Background Choking is one of the leading causes of death among unintentional injuries in young children. Food choking represents a considerable public health burden, which might be reduced through increased effective preventative education programs. We present a protocol for a community intervention trial termed CHOP (CHOking Prevention project) that aimed to teach Italian families how to prevent food choking injuries and increase knowledge relating to nutrition. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
0
23
0
2
Order By: Relevance
“…The prevention policies recently implemented in Italy have raised public awareness about the serious complications arising from the ingestion of batteries and magnets [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention policies recently implemented in Italy have raised public awareness about the serious complications arising from the ingestion of batteries and magnets [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, recent efforts were made on regulations, disseminating activities (safe food), and targeted initiatives to schools. For example, the Italian Choking Prevention project (CHOP) [ 19 ] was established to identify the most effective educational strategy for preventing FB injuries. The prevention policy’s actions should also consider the parent’s risk perception, which is an essential and culture-related element [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CHOP project was designed as a community intervention trial to compare three different school-based intervention strategies and is described elsewhere (Lorenzoni et al, 2019); trial profile is reported in Figure 1. The project delivered education on primary and secondary food choking prevention under the umbrella topic of nutrition education.…”
Section: Methodsmentioning
confidence: 99%
“…However, three of forty-four schools withdrew the consent after the randomization was done (Figure 1). The eligibility criteria for school participation are detailed elsewhere (Lorenzoni et al, 2019).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation